Strengthening Religious Harmony in Indonesia through Islamic Religious Education - Ahmad Asroni (Yayasan Azhar Amanaa Yogyakarta, 2025)
Indonesia is widely recognized as one of the largest multicultural countries in the world. While such plurality constitutes an important sociocultural asset, it simultaneously presents serious challenges related to intolerance, religious radicalism, identity politics, and social conflict. In this context, Islamic Religious Education (IRE) occupies a strategic role in promoting religious harmony through the cultivation of inclusive religious understanding, multicultural awareness, and moderate Islamic values. This study aims to analyze the implementation of IRE in strengthening religious harmony in Indonesia. This study employs a qualitative library research method by examining various academic sources, including books, scholarly journal articles, official government documents, and relevant research reports concerning IRE, religious moderation, multicultural education, and religious harmony. The analysis focuses on theological foundations, educational practices, and sociocultural challenges related to the implementation of IRE in Indonesia’s plural society. The findings reveal that IRE possesses substantial potential to strengthen religious harmony through the internalization of universal Islamic values such as tasāmuh (tolerance), wasathiyyah (moderation), ta‘āwun (mutual cooperation), justice, compassion, and social inclusivity. The implementation of IRE can be strengthened through multicultural-oriented learning, the reinforcement of religious moderation, transformative social practices, the exemplary role of educators, and contextual curriculum reform. However, the study also demonstrates that IRE continues to face significant challenges, including doctrinal-textual pedagogical orientations, exclusivist religious interpretations, the spread of radicalism, and the increasing influence of digital intolerance through social media platforms. Therefore, this article argues for the reconstruction of IRE toward a more contextual, dialogical, inclusive, and transformative educational paradigm capable of fostering democratic citizenship, social cohesion, and sustainable religious harmony within Indonesia’s multicultural society.